Magneto‐Optogenetic Deep‐Brain Multimodal Neurostimulation. (23rd October 2021) - Walton, Finlay; McGlynn, Eve; Das, Rupam; Zhong, Hongze; Heidari, Hadi; Degenaar, Patrick
Abstract : Electrical neurostimulation has been used successfully as a technique in both research and clinical contexts for over a century. Despite significant progress, inherent problems remain, hence there has been a drive for novel neurostimulation modalities including ultrasonic, magnetic, and optical, which have the potential to be less invasive, have enhanced biointegration, deeper stimulus penetration from the probe, and higher spatiotemporal resolution. Optogenetics—the optical stimulation of genetically photosensitized neurons, enables highly precise genetic targeting of the stimulus. Specifically, it allows for selective optical excitation and inhibition via different wavelengths. As such, optogenetics has become a prominent tool for neuroscience. Herein, the complementarity between different forms of neurostimulation is explored with a focus on cranial magnetic and optogenetic stimulation. Magnetic stimulation is complementary to optogenetics in that it does not require an electrochemical tissue interface like in the case of electrical stimulation. Furthermore, if incorporated onto the same probe as one with light emitters, its stimulation field can be orthogonal to the light emission field—allowing for complementary stimulus fields. Herein, dual optogenetic and magnetic modalities are proposed that can unite to yield a powerful and versatile tool for neural engineering. Abstract : Herein, the complementarity between forms of intracortical neurostimulation, focusing on magnetic and optogenetics, is studied. Magnetic microcoil neurostimulation complements optogenetics as it does not require an electrochemical tissue interface and its stimulation field can be orthogonal to that of an on‐device light source. The dual optogenetic and magnetic modalities that can yield a robust and selective tool for neural engineering are introduced.